2021
DOI: 10.1021/acs.jpcc.1c02064
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Kinetics, and Thermodynamics of Water and Its Ions at the Interface with Monoclinic ZrO2 Resolved via Ab Initio Molecular Dynamics

Abstract: In this work, we assess the structural, kinetic, and thermodynamic nature of water in contact with the monoclinic ZrO2 (1̅11) surface by ab initio molecular dynamics calculations. We find that water molecules in the first layer immediately facing the solid surface have a preferred orientation, with one water intramolecular bond, Ow–Hw, lying parallel to the surface, and the other water hydrogen Hw atom pointing away from the surface. This originates from the electrostatic attraction between surface Zr and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In this case of pH-neutral water, we observe an 8-order-of-magitude increase in the H + concentration in the Stern layer compared to bulk water, which is consistent with previous AIMD observation, which also predicts significant H + adsorption. 50 The multi-scale model enables us to quantify the concentration of surface adsorbates and how they change with pH and solid defect chemistry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case of pH-neutral water, we observe an 8-order-of-magitude increase in the H + concentration in the Stern layer compared to bulk water, which is consistent with previous AIMD observation, which also predicts significant H + adsorption. 50 The multi-scale model enables us to quantify the concentration of surface adsorbates and how they change with pH and solid defect chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…In this case of pH-neutral water, we observe an 8-order-ofmagitude increase in the H + concentration in the Stern layer compared to bulk water, which is consistent with previous AIMD observation, which also predicts significant H + adsorption. 50 Fig. 3 (a) Predicted water chemistry in equilibrium with ZrO 2 as a function of pH at room temperature.…”
Section: B Electrostatic Profile Across Zro 2 /Water Interface With C...mentioning
confidence: 99%
See 1 more Smart Citation
“…DFT studies have just recently begun to unravel the energetics and interfacial hydration structures of radiolytic species at interfaces of aluminum (oxy)­hydroxides, , WGO systems similarly relevant to managing radioactive waste. While equilibrium hydration structures and dynamics of MgO and ZrO 2 have been elucidated, mechanistic and dynamical studies of ET across semiconducting oxide–water interfaces have largely focused on nanoparticles and/or candidates for solar photocatalysis such as TiO 2 . Such studies have nonetheless demonstrated that the interplay between electronic energy levels and water dynamics governs interfacial charge transfer. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Zirconium alloys are widely used in nuclear reactors as fuel cladding and structural materials because of their lower thermal neutron absorption cross section, excellent corrosion resistance, and good compatibility with UO 2 . During the operation of the nuclear reactors, the zirconium claddings are oxidized by a primary coolant. Simultaneously, the zirconium claddings also absorb a fraction of hydrogen, which is released by the corrosion reaction of zirconium with water.…”
Section: Introductionmentioning
confidence: 99%